ANALISIS PERILAKU PASAR PAKAN DAN DAGING AYAM RAS DI INDONESIA: PENDEKATAN MODEL EKONOMERIKA SIMULTAN (FEED AND CHICKEN MEAT MARKETS BEHAVIOR ANALYSIS IN INDONESIA: SIMULTANEOUS ECONOMETRIC MODEL APPROACH)) - KETUT KARIYASA; BONAR M. SINAGA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2007)
ABSTRACT The aims of research on “Feed and Chicken Meat Markets Behavior Analysis in Indonesia” are to analyze: (1) domestic feed market behavior influence factors, (2) domestic and world markets of chicken meat behavior influence factors, and (3) responsive level each market to its influence factors. The simultaneous equation econometric model approach through the Two Stage Least Squares (2SLS) estimation method had been implemented in order to reach the objectives this research. The analysis results shown that feed production behavior is more responsive to changing the maize price than the price of feed itself, feed demand behavior is more responsive to changes in the chicken meat price than the price of feed itself, and feed price behavior is more influenced from supply side than demand side. Production and chicken meat are more influenced by its domestic price than other factors. In the long-run, the world price of chicken meat will be strongly influenced both from supply and demand sides, as well as it through import price has a stronger effect than the domestic market power to create the domestic chicken meat price . Keywords: Behavior, Mmarket, Feed, Chicken Meat, Elasticity, 2SLS, Indonesia ABSTRAK Tujuan penelitian tentang “Analisis Perilaku Pasar Pakan dan Daging Ayam Ras di Indonesia” adalah menganalisis: (1) faktor-faktor yang mempengaruhi perilaku pasar pakan domestik, (2) factor-faktor yang mempengaruhi perilaku pasar daging ayam domestik dan dunia, dan (3) tingkat respon masing-masing pasar terhadap factor-faktor yang mempengaruhinya. Pendekatan model ekonometri persamaan simultan melalui metode estimasi Two Stateg Least Squares (2SLS) diterapkan untuk mencapai tujuan penelitian. Hasil analisis menunjukkan bahwa perilaku produksi pakan adalah lebih responsive terhadap perubahan dalam harga daging ayam dari pada harga pakannya, dan perilaku harga pakan adalah lebih banyak dipengaruhi dari sisi penawaran dari pada sisi permintaan. Produksi dan daging ayam adalah lebih besar dipengaruhi harga domestiknya dari pada faktor-faktor lainnya. Dalam jangka panjang, harga daging ayam dunia akan menjadi kuat dipengaruhi baik dari sisi penawaran dan permintaan, maupun melalui harga import memiliki pengaruh lebih kuat dari pada kekuatan pasar domestik untuk menciptakan harga daging ayam domestik . Kata kunci: Perilaku, Pasar, Pakan, Daging Ayam, Elastisitas, 2SLS, Indonesia